Fraudulent Financial Statement: Analisis Fraud Hexagon (Studi Empiris pada Perusahaan Badan Usaha Milik Negara Sektor Non Keuangan yang Terdaftar di Bursa Efek Indonesia (BEI) Tahun 2022-2024) - Nurliyanti Rahma; Makhdalena Makhdalena; Fenny Trisnawati (Jaanur Elbarik Indonesia, 2026)
This study aims to determine the effect of the fraud hexagon on fraudulent financial statements in state-owned enterprises (SOE) in the non-financial sector listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. This study uses a quantitative approach with secondary data obtained from annual financial reports. The population in this study consists of 13 companies with a total of 39 companies. The variables used in this study are external pressure, nature of industry, change in auditor, change in director, frequent number of CEO's pictures and political connections as independent variables while fraudulent financial statements as the dependent variable. Data analysis techniques were carried out using path analysis with the help of SPSS version 27. The results of the study indicate that simultaneously, external pressure, nature of industry, change in auditor, change in director, frequent number of CEO's pictures and political connections have a significant influence on fraudulent financial statements with a coefficient of determination (R2) of 0.510 or 51%. Partially, it shows that external pressure, nature of industry and change in auditor influence fraudulent financial statements with a negative relationship and change in director, frequent number of CEO's pictures and political connection influence fraudulent financial statements with a positive relationship.